Effects of Digital Technologies on Zimbabwean Adolescent Lives During the COVID-19 Era: Pros and Cons - Chawarura, Wilfreda I; Zhou, Munyaradzi; Matsika, Cyncia; Zhou, Tinashe Gwendolyn (IGI Global, 2022)
The chapter focuses on the effects of using digital technology amongst Zimbabwean adolescents. The research was necessitated by the fact that adolescents are a vulnerable group still in the self-discovery age. COVID-19 pandemic resulted in the widespread use of digital learning to facilitate learning, communication, and social interaction among adolescents. Focus groups and interviews were used to gather data in primary schools. There is a disparity in technological device use and access to the internet between urban and rural areas dwellers. Ninety percent of students in rural areas did not have access to technological devices, and during the pandemic, they hardly used them for learning purposes but mostly used them for communicating with relatives. In Zimbabwe, digital technology devices have not yet replaced social relationships as most adolescents are restricted to 2-3 hours on their devices. A model for effective use of digital technologies in adolescents can be developed and implemented.